From Issue to Policy: Agenda Setting in Padang City Spatial Planning - Billy Febrima Hidayat; Asrinaldi Asrinaldi; Roni Ekha Putera (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
Regional spatial planning is a strategic public policy involving various interests and actors with a long-term orientation. However, in practice, spatial planning policies often face inconsistencies between regulatory objectives and regional development dynamics. This article aims to analyse the agenda-setting process in Padang City's spatial planning policy by examining how public issues are constructed, prioritised, and formulated into policy through the Padang City Regional Spatial Plan (RTRW) for 2010–2030. This research uses a qualitative approach, utilising a case study method. Data were collected through in-depth interviews, document studies, and policy tracing. The analysis was conducted using the concept of Agenda Setting Stages by Andersin and the concept of Agenda Setting by Nikolaos Zahariadis to explain and understand the patterns of interaction and interrelationship between official (within the government) and unofficial (outside the government) actors in policy formulation. The results indicate that the spatial planning agenda in Padang City is shaped by the dynamics of interactions among government, political, and non-governmental actors, with a dominant focus on economic development and investment interests. Development processes tend to prioritise technocratic and political considerations, while disaster mitigation and public interest are often neglected. These findings confirm that the agenda-setting process plays a crucial role in determining the direction and quality of regional spatial planning policies and has implications for the consistency of spatial planning policy implementation.